European Training Requirements in Neonatology 2021: the ESPR, EAP, and UEMS accredited European syllabus for neonatal training - Roehr, CC; Szczapa, T; Stiris, T; Hadjipanayis, A; Koletzko, B; Ross-Russell, R; Hüppi, P; Wellmann, S; Vento, M; European Board of Neonatal & Child Health Research (EBNCHR); European Society for Paediatric Research (ESPR); European Academy of Paediatrics (EAP); et al. (Karger Publishers, 2024)
Introduction: The European Union stipulates transnational recognition of professional qualifications for several sectoral professions, including medical doctors. The Union of European Medical Specialists (UEMS), in its “Charter on Training of Medical Specialists,” defines the principles for high-level medical training. These principles are manifested in the framework for European Training Requirements (ETR), ensuring medical training reflects modern medical practice and current scientific findings. In 1998, the European Society for Paediatric Research developed the first ETR for Neonatology. We present the ETR Neonatology in its third iteration (ETR III), ratified by the European Academy of Paediatrics (EAP), and approved by UEMS in 2021.